2017
DOI: 10.1080/07380577.2017.1335922
|View full text |Cite
|
Sign up to set email alerts
|

Adaption to Stroke: A Nonlinear Thinking Approach in Occupational Therapy

Abstract: This paper explores the role of perturbance and attractor, two key nonlinear features described by the Neuro-occupation model in shaping human behavior. A convenience sample of eleven Iranian participants who had both strokes and demonstrated high resilience were recruited for this study. To explore the process of how participants fell under the influence of the perturbance and attractor, the content analysis with pre-determined categories using deductive reasoning was used. The findings suggest that perturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…This finding supports previous qualitative research in which the IMP concepts were presumed to have had theoretically-based relationships [7][8][9]. There are several possible explanations to be considered for this result.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding supports previous qualitative research in which the IMP concepts were presumed to have had theoretically-based relationships [7][8][9]. There are several possible explanations to be considered for this result.…”
Section: Discussionsupporting
confidence: 89%
“…The findings showed that the relationships among the IMP variables have been either effective or ineffective, of which the results would lead to two different types of behavior called flexible or inflexible [8]. There was a study of 11 patients with strokes who were all highly resilient and seemed to be invested effectively in harmonious relationships among deliberate decisions, admissible meanings, and realistic perceptions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meaning refers to the ability to assimilate meaning following one’s performance. Perception is known as one’s attitude, feeling and beliefs that form one’s self-perceived concept ( Derakhshanrad et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…Two key properties of the model, known as "perturbance" and "attractor", were substantiated by the limited qualitative research with an objective to begin the process that led the subjects with cerebro-vascular strokes to initiate a positive change in their motor control [8]. Accordingly, perturbance has been acknowledged to have contributed to positive changes by providing influential opportunities or experiences to the clients, thereby receiving appreciation as an important property for their change [8].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, perturbance has been acknowledged to have contributed to positive changes by providing influential opportunities or experiences to the clients, thereby receiving appreciation as an important property for their change [8]. Attractor was reported to be a preferred mental state that enticed or attracted clients to make an intentional action, engage in meaningful occupational performance, and develop realistic beliefs that altered their perception [8].…”
Section: Introductionmentioning
confidence: 99%